Breaking Boundaries 2022
DOI: 10.31274/itaa.13446
|View full text |Cite
|
Sign up to set email alerts
|

Amazon’s Influence: The Online Apparel Purchase Intention of Amazon Prime and Non-prime Shoppers

Abstract: Introduction: Amazon, the world's largest e-commerce marketplace, represents a 50% share of the United States (U.S.) e-commerce market and inspires intense loyalty among shoppers with its Prime membership program (Chen et al., 2016). Both Amazon and Amazon Prime have grown in popularity and have completely transformed consumer expectations for online shopping (Wilson, 2018). As Amazon's dominance made it harder for retailers to meet consumers' expectations, many prominent retailers are closing stores or filing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…These results are inconsistent with those found by Alreck & Settle (2002) and (Escobar-Rodríguez & Bonsón-Fernández, 2017); the latter found that time-saving is a critical antecedent that predicts perceived value and the last effects online fashion purchase intention. However, they are consistent with those found by Rashaduzzaman (2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are inconsistent with those found by Alreck & Settle (2002) and (Escobar-Rodríguez & Bonsón-Fernández, 2017); the latter found that time-saving is a critical antecedent that predicts perceived value and the last effects online fashion purchase intention. However, they are consistent with those found by Rashaduzzaman (2020).…”
Section: Discussionsupporting
confidence: 93%
“…Online shopping allows consumers to save time as they do not need to visit one physical store to another, and they can obtain information about products and their prices from multiple sources in minutes. This time-saving feature increases consumers' shopping satisfaction, thus increasing purchase intention from online stores (Rashaduzzaman, 2020).…”
Section: 4mentioning
confidence: 99%
“…Based on the SEM analysis, CON presented the greatest influence on street food purchase intention through ATT (β = 0.746 and p = 0.007), SN (β = 0.696 and p = 0.016), and PBC (β = 0.477 and p = 0.008). The indicators, similar to other studies [100][101][102], showed that street foods are easily available with a lot of variety, and streets are filled with vendors selling street foods that fit consumers' schedules. In people's fast-paced environments, convenience plays a key role in making decisions [100], such as eating street foods rather than cooking at home or dining out in restaurants [101,102].…”
Section: Discussionsupporting
confidence: 81%
“…The indicators, similar to other studies [100][101][102], showed that street foods are easily available with a lot of variety, and streets are filled with vendors selling street foods that fit consumers' schedules. In people's fast-paced environments, convenience plays a key role in making decisions [100], such as eating street foods rather than cooking at home or dining out in restaurants [101,102]. These studies also provided insights into the significant positive indirect influence of CON on INT (β = 0.711 and p = 0.013).…”
Section: Discussionsupporting
confidence: 81%
“…Convenience reflects how easily consumers can find the products or services they require on the website [27] . In addition, studies have shown that the majority of respondents employed digital marketing for a variety of reasons, one of which was time-saving [28,29] . Another study has found that time-saving has a positive correlation with online buying intention (Jati, et al, 2020) [30] .…”
Section: Product Attributesmentioning
confidence: 99%